2010
DOI: 10.1094/pdis-94-6-0648
|View full text |Cite
|
Sign up to set email alerts
|

Crown Rot of Bananas: Preharvest Factors Involved in Postharvest Disease Development and Integrated Control Methods

Abstract: Crown rot is a complex disease that affects export bananas in all banana-producing countries. Usually invisible when the fruits are packed for transportation from tropical countries to distant destinations, disease symptoms occur during shipment, ripening, and storage. This disease, characterized by rot and necrosis, affects tissues joining the fingers with each other, called the crown. It may reach the pedicel and even the banana pulp when crown rot is severe. Losses from 10 to 86% have been recorded for trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 68 publications
2
28
1
1
Order By: Relevance
“…These findings show that the implementation of alternative control methods in the framework of an integrated management strategy (Lassois et al, 2010b) should perform better in highlands and particularly during the drier months of the year than in the rainy season. Our results also suggest a possible influence of black leaf streak disease that should be further studied.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings show that the implementation of alternative control methods in the framework of an integrated management strategy (Lassois et al, 2010b) should perform better in highlands and particularly during the drier months of the year than in the rainy season. Our results also suggest a possible influence of black leaf streak disease that should be further studied.…”
Section: Discussionmentioning
confidence: 84%
“…This quality potential would include two components: the fruit susceptibility to the post-harvest diseases (physiological component) and the level of fruit contamination by fungal pathogens (pathological component). Both components depend on pre-harvest factors including agronomic practices and soil-climate factors (Chillet & de Lapeyre de Bellaire, 1996;Chillet et al, 2000;Lassois et al, 2010b). Alternative control methods as well as any control measures should rely on a better understanding of these pre-harvest factors as previously shown for wound anthracnose, another post-harvest disease of bananas (de Lapeyre de Chillet et al, 2006Chillet et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…These post-harvest diseases are responsible for 25 to 30% of banana losses in India (Kachhwaha et al, 1991), 5 to 25% in developed countries (Khader, 1992) and 30 to 60% in Senegal (Zakari, 2007). The fungal strains responsible for such post-harvest losses of bananas vary according to production zones and seasons (Lassois et al, 2010). In Costa Rica, Musicillium theobromae, Colletotrichum musae, Ceratocystis paradoxa, Lasiodiplodia theobromae, Nigrospora sphaerica, Cladosporium sp., Penicillium sp., Acremonium sp., Aspergillus sp., as well as several species of Fusarium, namely F. semitectum, F. oxysporum, F. solani, etc.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Crown rot disease affects export banana fruit in all producing countries and is considered to be one of the main postharvest diseases of banana (Lassois et al 2010b). The symptoms appear on the crown (i.e., the tissue joining the fruit pedicels with each other).…”
mentioning
confidence: 99%
“…It has been suggested that these spatiotemporal fluctuations reflect the variations in the banana fruit quality potential that elaborates during preharvest stages (Lassois et al 2010b). This quality potential depends on both physiological and parasitic components which, in turn, are influenced by agrotechnical and soil-climate factors.…”
mentioning
confidence: 99%